Family as the Place for National Discrimination: An Analysis of Beatrice Speraz’s Autobiography - Dalmazzo, Pietro (Quaderni d'Italianistica)

(untitled) (Iter Press, 2024)
This essay examines Beatrice Speraz’s autobiography, Ricordi della mia infanzia in Dalmazia (1915), which describes her childhood in Dalmatia and how the different nationalities of her parents—one Italian and the other Dalmatian—affected her life and self-perception. It looks at how the author portrayed the formation of her national identity through relational dynamics with her maternal aunt and her father and emphasizes how one of the semantic aspects of this process was eventually dismissed by the Italian side of her family. The essay delves into these issues by employing Adriana Cavarero’s understanding of relationality and contrapuntal reading as theorized by Edward Said in Culture and Imperialism (1994). Through these lenses, the essay underscores how Speraz represented her identity as the daughter of an Italian mother and a Dalmatian father, and the kind of relationship she established between her national identity, Italy and Dalmatia. Furthermore, the essay elucidates how Speraz’s familial relationships played a pivotal role in two processes: first, in fostering her belief that she was a participant in a historically equal relationship between Italians and Dalmatians; and second, in her dismissal as a “barbarian” because her father was Dalmatian.